Strategies and best practices in social innovation: an institutional perspective - Peris-Ortiz, Marta; Gómez, Jaime Alonso; Marquez, Patricia (Springer, 2018)
Presents different ways to design and develop social innovations in businesses and organizations Highlights elements of social innovation in higher education Examines social innovation in practice Features case studies from different regions around the world
Keywords: Idéation; dialogue et maillage; Mise en valeur; Réservé UdeM; UK